2020
DOI: 10.1002/1348-9585.12146
|View full text |Cite
|
Sign up to set email alerts
|

Long-term observation of pulmonary toxicity of toner with external additives following a single intratracheal instillation in rats

Abstract: Objectives Along with technological innovations for improving the efficiency of printing, nanoparticles have been added to the surface of toners, and there is concern about the harmful effects of those components. We investigated, through a long‐term observation following intratracheal instillation using rats, whether exposure to a toner with external additives can cause tumorigenesis. Methods Female Wistar rats were intratracheally instilled with dispersed toner at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the present study group, no significantly elevated levels were found in toner-handling workers, suggesting that exposure to toner does not induce interstitial pneumonia. With regard to the toxicity of toner particles, the results of rat intratracheal instillation and long-term inhalation exposure tests [35,36] suggest that the carcinogenicity of toner particles is not so apparent and that, as with general dust, the excess amount of inhalation exposure and duration of exposure are involved in lung damage.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study group, no significantly elevated levels were found in toner-handling workers, suggesting that exposure to toner does not induce interstitial pneumonia. With regard to the toxicity of toner particles, the results of rat intratracheal instillation and long-term inhalation exposure tests [35,36] suggest that the carcinogenicity of toner particles is not so apparent and that, as with general dust, the excess amount of inhalation exposure and duration of exposure are involved in lung damage.…”
Section: Discussionmentioning
confidence: 99%